Sự tái hòa nhập công việc và ý định rời bỏ tổ chức của các giảng viên đi học nước ngoài trở về - Hồ Thị Thúy , Nga; Lê Thị Mỹ , Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The objective of this paper is to study the impact of human resource practices towards improving organizational performance and organizational climate on work repatriation adjustment and turnover intentions of academic returnees after returning from studying abroad. Based on a sample of 242 academic returnees, this paper used the linear regression model and Baron and Kenny’s method to test the direct effects and mediation effects in the research model. The research results showed that organizational climate had the strongest impact on work repatriation adjustment and turnover intention, followed by skill-enhancing human resource practices, while motivation-enhancing human resource practices had no impact. Furthermore, work repatriation adjustment fully mediated the links of organizational climate and skill-enhancing human resource practices with turnover intention. Our study had contributions to both literature on international human resource management and practical implications for Vietnamese universities in assisting academic returnees’ work repatriation adjustment and in retaining this valuable human resource.
Keywords: Work repatriation adjustment; Turnover intention; Academic returnees; Human resource practices; Organizational climate